"A lot of people call it liquid handcuffs" – barriers and enablers to opioid replacement therapy in a rural area. (4th March 2019) - Wood, Penelope; Opie, Cynthia; Tucci, Joseph; Franklin, Richard; Anderson, Karen
ABSTRACT: Introduction: Opioid dependence is a complex health condition often requiring long-term treatment. The main objectives of treatment are to reduce dependence and the associated morbidity and mortality. Opioid replacement therapy (ORT) is an effective pharmacological therapy for opioid dependence. The aims of this research were to explore barriers and enablers to ORT in rural areas of Australia. Design and Methods: A qualitative study design incorporating semi-structured interviews was used to explore views of people in ORT. Interviews were analysed for emergent themes and issues. Results: Barriers to ORT were restrictiveness, stigma, the medication and structure of the program. Enablers were structure of the program, access to takeaway doses, effect on drug use and the medication. Discussion: To improve access and retention in ORT programs action is needed to facilitate programs meeting the needs of rural people, including reducing cost of medication, addressing the restrictiveness of programs and effect on employment opportunities, and stigma associated with drug use and addiction in communities. Conclusions: Barriers and enablers to ORT programs exist in the rural areas studied. Geographical distance, inability to gain and maintain social connections including employment, and lack of community education addressing stigma are significant barriers to ORT in these areas.